Sonographic and clinical characteristics of struma ovarii - Zalel, Y; Seidman, D. S; Oren, M; Achiron, R; Gotlieb, W; Mashiach, S; Goldenberg, M (Journal of ultrasound in medicine, 2000)
Our objective was to evaluate the preoperative clinical, laboratory, and sonographic characteristics of struma ovarii in comparison to ovarian dermoid cysts. A retrospective review of gynecologic patients operated on for mature cystic teratoma over a 10 year period identified 12 cases of struma ovarii. These cases, combined with 4 additional cases from an earlier report, were the subject of this study. Results were compared to 32 cases of ovarian dermoid cysts. Ovarian struma ovarii occurred in 12 (4.8%) of 251 cases of ovarian dermoid cysts. Most patients were premenopausal, and the mean lesion diameter was 57.3 mm (range, 30‐95 mm). Struma ovarii occurred more frequently (68.8%) in the right adnexa and was seen with a normal CA‐125 level. Blood flow, assessed by Doppler ultrasonography, was located in the center of the lesion in all cases of struma ovarii. Rare cases were seen with elevated tumor markers and low resistance blood flow. With regard to dermoid cysts, blood flow had a higher resistive index. In addition, no blood flow could be detected from the center of the echoic lesion in dermoid cysts (P < 0.0001). In summary, it is difficult to distinguish between struma ovarii and dermoid cysts on the basis of their sonographic appearance. Nevertheless, Doppler flow may aid in the preoperative diagnosis of struma ovarii. Blood flow signals, detected from the center of the echoic lesion, and low resistance to flow may be more common in struma ovarii.